Improved Science Learning Outcomes Through Teams Game Cooperative Learning Tournament - Dwi Putri Winanti; Baskoro Adi Prayitno; Lina Mahardiani (Postgraduate, University of Mataram, 2022)
This research is an attempt to describe the increase of interest in Science of students of class VIII at SMP Negeri 2 Colomadu after the application of Teams Games Tournament (TGT) learning model. This research uses Class Action Research (PTK) method which includes planning, action, observation and reflection. The subjects in this study were students of class VIII at SMP Negeri 2 Colomadu, which amounted to 31 students. The object of this study is interest in learning science of students through Teams Games Tournament learning model (TGT). Data is fed by observation, test and documentation. Data analysis using comparative descriptive analysis technique with percentage. The results of this study indicate an increase in learning achievement of science students. This can be seen from the average score of learning achievement of science students also experienced an increase before the action of 68, in the first cycle of 75.5 and on the second cycle of 80.8. In addition, the percentage of students' learning mastery, example before the action of 63%, in the first cycle of 75% and in the second cycle of 94.75%. So it can be concluded that